STUDY ON POTENTIAL FEASIBILITY OF AQUACULTURE LAND USING GEOGRAPHIC INFORMATION SYSTEM (GIS) IN NORTH SEMARANG SEA - Adamimawar, Ceteria Nuchter Ikbar; Jailani, Abdul Qadir; Aji, Muhammad Tri (Asian Journal of Aquatic Sciences, 2022)
Marine culture in the North Semarang area is still not optimally utilized by the surrounding community. The selection of the location of aquaculture activities is needed to determine the feasibility of suitable land for aquaculture in the sea. However, due to the large number of fishing activities, ports, and dense settlements have an impact on water quality which affects marine aquaculture activities. The purpose of this study was to determine the condition of the waters, determine the level of land suitability using GIS, and the area of ​​land that can be used as a location for marine culture in the waters of North Semarang. The method used is by scoring and GIS. Parameters observed included protection, brightness, temperature, depth, current velocity, substrate, wave height, salinity, DO, BOD, COD, and pH. Furthermore, a scoring calculation is carried out to determine the suitability value which is then processed using GIS to produce a suitability map. The results showed that North Semarang waters were classified as S2 class (quite suitable) for marine aquaculture activities and with an area of ​​250,000 ha.